Exploring heavy metal dynamics and risks from dust and soil in urban cities of Jharkhand, India - Arpita Roy; Tanushree Bhattacharya; Mala Kumari; Abhishek Kumar (Scientific Reports)
Abstract Jharkhand is a minerally prosperous state with geogenic and industrial origins of metals. This study assesses the seasonal variation of pseudo-total metal contents (Cr, Ni, Pb, Zn, Mn, Cu, Fe, Mg, Al) and related contamination and risks in indoor dust, street dust, and soils of four major cities of Jharkhand. Across cities and seasons, Zn, Cu, and Pb were the most common pollutants. Indoor dust showed higher metal concentrations than street dust and soil, suggesting their indoor origins. Geo-accumulation indices indicated significant Cu contamination, followed by Pb and Zn. Street dust exhibited notable enrichment in Zn and Pb in all cities except Dhanbad, where Cu contamination was substantial. Ecological risk indices peaked during summer in street dusts of Ranchi and Bokaro (for Pb) and during monsoons in soils of Jamshedpur and Dhanbad (for Cu). Based on chemical sequential extractions, the mobilities of Mg, Mn, Zn, and Cu were high, while Pb had moderate mobility. The probable sources of immediate concern were vehicles and paints, wire, electroplating, metal casting, and steel manufacturing industries. The findings emphasize the urgent need for implementing stringent regulations to mitigate metal emissions and ensure compliance with environmental standards.